Re-Desain Struktur Atas Tahan Gempa Gedung Apartemen Berdasarkan Sni 1726:2019 Di Kota Semarang - Aldino Daffa Cahya Pratama; Muhammad Naufal ArRasyid (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Indonesia lies within a region of high seismic activity; therefore, the structural design of buildings must adequately account for earthquake effects. The apartment building located in the city of Semarang is a four-story residential structure constructed in 2023 and originally designed in accordance with SNI 1726:2012 provisions. With the enactment of SNI 1726:2019 as the latest regulatory standard, a structural reassessment and redesign of the building’s superstructure are required to ensure its safety level and structural performance under seismic loads. This study aims to redesign the superstructure of the apartment building, including beams, columns, and slabs, using the Special Moment Resisting Frame System (SMRF) in compliance with SNI 1726:2019, SNI 1727:2018, and SNI 2847:2019. Structural analysis was conducted using both the equivalent static method and response spectrum analysis with the aid of ETABS software. Seismic parameters were determined based on the site conditions, assuming a soft soil classification (Site Class SE). The design results indicate that the building structure satisfies seismic resistance requirements, as evidenced by the magnitude of the design earthquake forces, inter-story drift limits, and the ductility provisions of the SMRF system. The redesigned dimensions and reinforcement detailing of structural elements—columns, beams, and slabs have been adjusted to fulfill the strong column–weak beam principle. Therefore, the redesigned superstructure of the apartment building, based on SNI 1726:2019, is deemed safe and capable of enhancing structural performance against earthquake effects.